New FeI–FeI Complex Featuring a Rotated Conformation Related to the [2 Fe]H Subsite of [Fe–Fe] Hydrogenase. Issue 46 (14th October 2013) - Munery, Sabrina; Capon, Jean‐François; De Gioia, Luca; Elleouet, Catherine; Greco, Claudio; Pétillon, François Y.; Schollhammer, Philippe; Talarmin, Jean; Zampella, Giuseppe
<x xml:space="preserve">Abstract</x> Rotated geometry: The first example of a dinuclear iron(I)–iron(I) complex featuring a fully rotated geometry related to the active site of [Fe–Fe] hydrogenase is reported (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>